Antibacterial and sporicidal activities of Syzygium polyanthum L. extract against Bacillus cereus isolated from rice - Rukayadi, Yaya; Ramli, Suzita; Lau, Kah Yan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Spore-forming bacteria, Bacillus sp., frequently been associated with the contamination of rice and other starchy products. Spores are more resistant to antimicrobial treatments than its vegetative cells. The extract of Indonesian bay leaf (Syzygium polyanthum L.) was assessed for its antibacterial and sporicidal activities against vegetative cells and spores of B. cereus isolated from rice (25 strains). The results showed that S. polyanthum L. extract was able to inhibit the growth of vegetative cells of all B. cereus isolates with MICs ranged from 0.16 to 0.63 mg/mL and can kill with MBCs ranged from 0.31 to 2.50 mg/mL. The bactericidal endpoint for B. cereus BC-NP.8 in time kill curve was at 1.25 mg/mL (8× MIC) after 4 h of incubation while for B. cereus ATCC 33019 was at 2.50 mg/mL (8× MIC). The sporicidal activity of S. polyanthum L. extract was not affected by different temperatures treatment and alteration of the pHs of extract. Therefore, this indicates that the extract was stable after exposed to pH3, 7 and 10 as well as temperature of 50, 80, and 121°C. Observation under on scanning electron microscope the structure of the B. cereus ATCC 33019 spores was ruptured after being treated with 1% (w/v) S. polyanthum L. extract for 1 h. In conclusion, S. polyanthum L. extract had antibacterial and sporicidal activity against vegetative cells and spores of B. cereus isolated from rice.